Urgensi Perceraian di Peradilan Agama - Zurifah Nurdin (Institut Agama Islam Negeri Bengkulu, 2014)
Essentially divorced may, but shall not home when going without seeing the considerations, therefore, to neutralize the arbitrariness of the divorce. It is necessary to take care of that institution. In this paper will divorce issues before the court in terms of (1) juridiction; (2) normative (QUr'an and Hadith); (3) ushul fiqh (maqashid al Shar'ie and aslahah mursalah); (4) positive and negative impacts of divorce in court.